Network Pharmacology and Comparative Transcriptome Reveals Biotargets and Mechanisms of Curcumol Treating Lung Adenocarcinoma Patients With COVID-19 - Yang, Lu; Xiong, Hao; Li, Xin; Li, Yu; Zhou, Huanhuan; Lin, Xiao; Chan, Ting Fung; Li, Rong; Lai, Keng Po; Chen, Xu (Frontiers in Nutrition, 2022)
The coronavirus disease of 2019 (COVID-19) pandemic has led to 4,255,892 deaths worldwide. Although COVID-19 vaccines are available, mutant forms of SARS-CoV-2 have reduced the effectiveness of vaccines. Cancer patients are more vulnerable to COVID-19 than patients without cancer. Identification of new drugs to treat COVID-19 could reduce mortality rate, and traditional Chinese Medicine has shown potential in COVID-19 treatment. In this study, we focused on lung adenocarcinoma (LUAD) patients with COVID-19. We aimed to investigate the use of curcumol, a traditional Chinese medicine, to treat LUAD patients with COVID-19, using network pharmacology and systematic bioinformatics analysis. Results showed that LUAD and COVID-19 patients share a cluster of common deregulated targets. Network pharmacology analysis identified seven core targets (namely, AURKA, CDK1, CCNB1, CCNB2, CCNE1, CCNE2, and TTK) of curcumol in patients with COVID-19 and LUAD. Clinicopathological analysis of these targets demonstrated that the expression of these targets is associated with poor patient survival rates. Bioinformatics analysis further highlighted the involvement of this target cluster in DNA damage response, chromosome stability, and pathogenesis of LUAD. More importantly, these targets influence cell signaling associated with the Warburg effect, which supports SARS-CoV-2 replication and inflammatory response. Comparative transcriptomic analysis on in vitro LUAD cell further validated the effect of curcumol for treating LUAD through the control of cell cycle and DNA damage response. Current study supports the earlier findings that curcumol is a potential treatment for LUAD patients with COVID-19.